Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:• Strategic Planning in Public Secondary Schools in the Southern Governorates of Palestine  and its Relationship to Competitive AdvantageMr. Bahaa Darwish Alghirbawi,Ms. Zenat Hamed Kuhail, Prof. Sleman Hussein Al-Mozeyn• Obstacles to developing cognitive creativity among secondary school students in Al-Baha region from the perspective of their teachers and ways to address them in light of Vision 2030 and contemporary global trendsMr. Ibrahim Mubarak Ahmed Al-Zahrani• The Relationship between Teachers' Spatial Job Stability and Job Performance: An Analytical Field Study in Muscat Governorate Schools in the Sultanate of OmanDt. Mohammed Suleiman Al-Baluoshi• Perceptions of Self-Evaluation Team Members Regarding Implementation Challenges: A Qualitative Study Based on the Experience of Self-Evaluation in Primary Schools in Southern Khamis MushaitMs. Sarah Ajlan Al-Shahri• Talent Management: From Emergence to Development (A Conceptual Study of the Term and Its Dimensions)Mr. Sami Hamed Almalki• Emotional Exhaustion and Its Relationship with Professional Performance Among Faculty Members of the College of Education at the University of HailMs. Rehab Mujzi Al-Shammari ,Ms. Malkah Murdi Al-Mutawea ,Ms. Bashayr Nawaf Assaf Al-Shammari• Self-compassion and its relationship to psychological well-being among female students  at the University of HailMs. Rehab Mujzi Alshammari• Interventions to Promote Executive Development in Children and AdolescentsMs. Elmoujahid Oumaima
Keywords: Journal of Educational and Psychological Sciences